USEFULLNESS OF A NEW POLYURETHANE VASCULAR ACCESS GRAFT AS AN ARTERIOVENOUS FISTULA FOR HEMODIALYSIS - TANAKA, Noriaki; OKA, Yoshinari; MATSUDA, Hiroaki; MIYAZAKI, Masashi (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 1999)
We evaluated a new polyurethane vascular access graft (Thoratec Vascular Access Graft, TVAG) as a vascular access for hemodialysis. Subjects were 16 patients with chronic renal failure and TVAG was implanted as arteriovenous fistula in them. These were one case of loop in the fore arm, one case of a loop in the upper arm, eight cases of straight in the upper arm and six cases of loop configuration in the thigh. TVAG is characterized by its elasticity and self-sealing property that require careful subcutaneous positioning of TVAG and deliberate sutures during anastomosis, but it resulted in no postoperative limb edema and easy hemostasis after needle removal in our subjects. These findings indicate that TVAG can be used for hemodialysis in early postoperative days. In our cases, hemodialysis was able to start with in 4 days after implantation of TVAG, with an average of 2.4 days. Shorter hospital stay is consequently expected. Early occulusion of fistula due to thrombosis occurred in two cases. Thrombectomy was easily performed in both cases using Fogarty balloon catheters and they could be used for hemodialysis again. It is concluded that TVAG is useful as a vascular access for hemodialysis. Further assessment of its long-term patency and possible complications are necessary.